Book‐to‐Market Components, Future Security Returns, and Errors in Expected Future Earnings - Billings, Bruce K.; Morton, Richard M. (Journal of Accounting Research, 2001)
This study investigates whether the ability of book‐to‐market to predict returns derives from systematic errors in the market’s expectation of future earnings. We extend Beaver and Ryan (1996, 2000) by decomposing book‐to‐market into a more persistent (bias) component and a delayed recognition (lag) component. We find that both components are related to analyst expectations of future earnings, but the lag component is the dominant factor across all forecast horizons. Similarly, we find that the lag component explains most of the inverse relation between book‐to‐market and future returns. Given that lag is constructed by regressing book‐to‐market ratios on lagged price changes, our results are consistent with the lag component capturing systematic stock price reversals. We find that the components have unique relations with subsequent earnings forecast revisions, and controlling for these relations substantially mitigates the components’ ability to predict returns. Our component‐level analysis provides insight into how expected future earnings, summarized in book‐to‐market ratios help to explain this market anomaly.